Qualidade fisiológica e avaliação de bioprodutos no controle de Colletotrichum lindemuthianum em sementes de feijão - comum - Moreira, Thainá Fogliatto (2021)
Anthracnose caused by Colletotrichum lindemuthianum (Sacc & Magn.) Lams.-Scrib. is considered one of the most important diseases of bean culture, causing losses of up to 100% when contaminated seeds and favorable conditions for the development of the pathogen during the crop cycle are used. This disease is seen as difficult to control due to its high genetic variability, survival in cultural remains and by transmission via seeds. Integrated and complementary measures for its control present satisfactory results, such as genetic, cultural, physical, chemical and biological measures. The use of chemical fungicides are not totally efficient in the control of this pathogen, and can also cause negative impacts in the most different compartments of the ecosystems. Therefore, biological control emerges as an alternative to control this disease through the use of antagonistic microorganisms. Among the most studied microorganisms for the biological control of diseases the species of the gender Trichoderma are distinguished being this the most used in Brazil and in the world, whose results of researches have been demonstrating the effectiveness of the fungus Trichoderma spp, on several phytopathogens of soil and aerial part, causing the reduction of the incidence. In front of that this work had with objectives to evaluate: i) the physiological and sanitary quality of seeds of commercial cultivars of common bean; ii) the antagonistic and inhibitory effect of active metabolites of different strains of Trichoderma spp, in the control of C.lindemuthianum in vitro.iii)- the effect of seed treatment with bioproducts based on Trichoderma spp. on the physiological quality of kidney bean seeds and control of Colletotrichum lindemuthianum race 81). Three experiments were conducted at the Federal University of Santa Maria, Frederico Westphalen/RS campus. In the first experiment the physiological and sanitary quality of seeds from five commercial cultivars of common bean was evaluated. The second experiment relied on direct confrontation, as well as the exposure of the pathogen to volatile compounds of different strains of Trichoderma spp. to the isolate of C. lindemuthianum. The third experiment evaluated the pathogenicity of C.lindemunthianum race 81 on common bean cultivars, as well as analyzing the effect of seed treatment with bioproducts based on Trichoderma spp. on pathogen control and on the physiological potential of the seeds. All bean cultivars analyzed presented high physiological quality seeds and within the minimum standard required by the Ministry of Agriculture for commercialization. As for the health of the bean seeds, they presented a high incidence of storage fungi that favored the reduction in physiological potential. All the isolates of Trichoderma presented antagonistic action on the mycelial growth of C lindemunthianum in the test of direct confrontation and antibiosis, when compared with the control. The isolates of Trichoderma harzianum / Stimucontrol® and T. Asperellum / Quality® showed a greater potential for biological control of the pathogen in vitro. The inoculation method of C. lindemuthianum race 81 in bean seeds, through the immersion of the seeds in the conidia solution provided low transmissibility of the pathogen.The bioproducts Quality® (Trichoderma asperillum) and Stimucontrol® (Trichoderma harzianum), via seed treatment, demonstrated potential for the protection of bean cultivars against anthracnose and are efficient in promoting plant growth under laboratory conditions. The cultivars Uiapuru, Urutau and Veloz demonstrated to be susceptible to Colletotrichum lindemuthianum race 81. The determination of the severity of anthracnose in contaminated and treated seeds in the greenhouse is proportional to the inoculation method. The environmental conditions (temperature and humidity), method of artificial inoculation and aggressiveness of the pathogen interfere in the severity of anthracnose, in greenhouse. Therefore, the association of control methods such as seed treatment and resistant cultivars promotes greater efficiency in the control of anthracnose in bean.